2023
DOI: 10.3389/fendo.2023.1134318
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-laden bone cement for diabetic foot infected wounds: A systematic review and meta-analysis

Abstract: ObjectiveA large body of literature has demonstrated the significant efficacy of antibiotic bone cement in treating infected diabetic foot wounds, but there is less corresponding evidence-based medical evidence. Therefore, this article provides a meta-analysis of the effectiveness of antibiotic bone cement in treating infected diabetic foot wounds to provide a reference basis for clinical treatment.MethodsPubMed, Embase, Cochrane library, Scoup, China Knowledge Network (CNKI), Wanfang database, and the Clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“… 28 Additionally, ALBC has been proven to rapidly control infection, promote ulcer healing, shorten hospital stays and lessen medical costs. 23 , 24 , 25 , 26 In our case series, the overall average hospital stay for patients was 18 days, which is lower than the 31 days (range: 12–51 days) reported in the systematic review by Bhat et al 29 Besides releasing antibiotics, the ALBC treatment for DFUs promotes the formation of the ‘induced membrane’ (Figure 2B ). 23 , 26 It can also cause the production of various cytokines, such as vascular endothelial growth factor (VEGF) and transforming growth factor‐β (TGF‐β).…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“… 28 Additionally, ALBC has been proven to rapidly control infection, promote ulcer healing, shorten hospital stays and lessen medical costs. 23 , 24 , 25 , 26 In our case series, the overall average hospital stay for patients was 18 days, which is lower than the 31 days (range: 12–51 days) reported in the systematic review by Bhat et al 29 Besides releasing antibiotics, the ALBC treatment for DFUs promotes the formation of the ‘induced membrane’ (Figure 2B ). 23 , 26 It can also cause the production of various cytokines, such as vascular endothelial growth factor (VEGF) and transforming growth factor‐β (TGF‐β).…”
Section: Discussionmentioning
confidence: 47%
“…Most DFU infections are polymicrobial, with Staphylococcus aureus , Pseudomonas aeruginosa and Escherichia coli being the primary pathogens. 21 , 22 In recent years, ALBC has been used to treat DFUs 23 , 24 , 25 , 26 as it is mixed with antibiotics such as gentamicin, tobramycin and vancomycin. 27 This mixture can continuously release antibiotics locally, slowly and effectively killing the bacteria commonly infecting DFUs, thus avoiding the systemic side effects of medications.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic antibiotics are used to treat diabetic foot infections in subjects, but prolonged use of these drugs might have negative side effects and lead to bacterial resistance 29 . Sun Shujuan et al's analysis of the pathogenic bacteria associated with diabetic foot in Beijing revealed a 16.9% prevalence of bacteria that were multi‐drug resistant 30 . Diabetic foot infection subjects place a large strain on clinical care due to their lengthy hospital stays, lengthy recovery from trauma and expensive medical costs.…”
Section: Discussionmentioning
confidence: 99%
“…Polymethylmethacrylate (PMMA)-based antibiotic-loaded bone cement (ALBC) is widely employed in orthopedic surgery all over the world [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. As an antibiotic carrier, ALBC provides local drug delivery at the surgical site in concentrations sufficient for the successful suppression of the infection (e.g., periprosthetic joint infection (PJI)) [ 2 , 6 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polymethylmethacrylate (PMMA)-based antibiotic-loaded bone cement (ALBC) is widely employed in orthopedic surgery all over the world [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. As an antibiotic carrier, ALBC provides local drug delivery at the surgical site in concentrations sufficient for the successful suppression of the infection (e.g., periprosthetic joint infection (PJI)) [ 2 , 6 , 9 , 10 , 11 , 12 , 13 ]. Moreover, ALBC application can be advantageous compared to systemic antibiotic administration since it provides higher local concentrations, lowers rates of antibiotic-associated adverse events, and decreases antimicrobial resistance via the preservation of the gastrointestinal microbiome [ 8 ].…”
Section: Introductionmentioning
confidence: 99%